Intercreditor Distribution in Sovereign Debt Restructuring - Mandeng, Ousmene (IMF Working Papers; Working Paper ;, 2004)
Intercreditor equity represents one of the main objectives of bankruptcy proceedings. Yet, recent restructurings of sovereign debt suggest that violation of intercreditor equity is common. While existing contractual provisions, and guidelines issued by creditor committees, establish fundamental principles about creditor treatment, they seem to remain too vague to guide debt restructuring processes effectively. The paper focuses on distribution, and argues that lack of clear guidelines for distribution may complicate and delay the resolution process and induce undue uncertainty about the predictability and viability of the restructuring outcome. The paper discusses and proposes parameters which may contribute to establishing explicit principles for the assessment of intercreditor equity in distribution.